Cation polarizability from first-principles: Sn2+ - Bernasconi, L; Wilson, M; Madden, P (2001)
Generalized Gradient Corrected Density Functional Theory calculations have been performed on SnO in the gas phase. The total charge density of the molecular system has been partitioned between Sn and O using a Wannier localization transformation of the Kohn Sham eigenvectors, and the single-ion dipole moment of Sn2+ at the optimized bond-distance has been estimated in terms of the position of the resulting Wannier function centers. This analysis has been extended over a wide range of ionic separations in order to monitor the dependence of the Sn2+ dipole on both Coulombic and short-range interactions with O2-. The mechanism responsible for Sn2+ polarization proves to be easily explained in terms of the non-bonding orbital center distance from the nucleus, without any major contributions deriving from mixing with orbitals centered on O. The Sn2+ polarizability in the molecular system at the optimized bond distance (15.23 a.u.) is intermediate between the value for the free-ion (14.50 a.u.) and the estimate for crystalline SnO in the rocksalt structure (15.83 a.u.). The bond-length dependent polarizability at large ionic separations shows excellent agreement with the available Hartree Fock free-ion value. © 2001 Elsevier Science B.V. All rights reserved.